PENERAPAN PENDEKATAN PROBLEM POSSING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Amelia, Risma; Aripin, Usman; Kirana, Yana Cahya (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The research aims to determine the enhancement of students ' mathematical problem solving skills. This research uses experimental methods. The population is a class VII junior high, while the sampling is a class VII one of the junior high schools in Cimahi, consisting of two classes, the VII E class being an experimental class while the VII D became the control class. Both classes were given pretes at the beginning of the meeting and Postes at the end of the meeting. The instrument used is 5 items about the mathematical troubleshooting description. Based on the Mann Whitney non parametric test that acquired significance was 0.000. The conclusion that resulted in this research is the enhancement of mathematical problem solving skills of students who are using the approach of possing problem better than using scientific approach. Learning using the approach trains the students in making problems and answering them so that mathematical problem-solving skills can increase.